The Insights, “Comfort” Effect and Bottleneck Breakthrough of “E-Commerce Temperature” during the COVID-19 Pandemic - Yixing Yang; Yanan Ma; Gang Wu; Qian Guo; Hongbo Xu (Journal of Theoretical and Applied Electronic Commerce Research, 2022)
The impact of the COVID-19 pandemic on fresh food e-commerce has led to a loss of consumers, and “e-commerce temperature” is seen as an important means of alleviating consumer dissatisfaction and retaining consumers. To explore the connotation and effect of it, and to break through possible “comfort” bottlenecks, we used online reviews of the Jingdong fresh food platform as research data, mined the characteristics of “e-commerce temperature” with the help of the LDA topic model, and evaluated the mechanism of “e-commerce temperature” on consumer satisfaction during the pandemic by using quasi-natural experiments and Word2vec-based sentiment analysis. The results show that “e-commerce temperature” has five connotations of logistics commitment, humanized delivery, health pledge, pandemic perseverance, and consumer care, which can effectively mitigate the loss of consumer satisfaction. Interestingly, we found that the “e-commerce temperature” has a limited “comfort” effect. Additionally, further social network analysis shows that the bottleneck is mainly due to the consumers’ psychological gaps when comparing the usual e-commerce services, and cretailers can repair them through financial compensation and spiritual solace. The study explores e-commerce service quality at different pandemic stages with the help of text mining techniques, enriches the theory of e-commerce research, and alleviates the Hawthorne bias in traditional empirical studies. This study also provides a reference for e-retailers to improve service quality and respond to emergencies in a changing post-pandemic era.